Model Branding Syariah dalam Praktik Periklanan Islami di Syafa’at Yogyakarta - Alma Mandjusri; Manik Sunuantari; Fachmi Ibrahim (Syntax Idea)
Sharia branding and Islamic advertising are interesting to research, considering that public perception of Islamic advertising often involves the use of Halal label symbols, hijabs, caps, sarongs and religious figures as influencers. This research explores more deeply the sharia branding model in Islamic advertising practices in Indonesia, especially the one developed by Syafa'at. This research uses a qualitative descriptive method with a single case study approach. The primary data collection technique is through in-depth interviews with the CEO of Syafa'at, employees, several Syafa'at clients and a religious teacher who understands muamalah fiqh. Secondary data was taken from the Syafa'at website and documentation. The data analysis method uses reduction, description and drawing conclusions. The results of the research found that the sharia branding model developed by Syafa'at started from a collaborative relationship with the client through the syirkah system, and to build sharia branding using 2 strategies, namely 1) Aqliyah Islamiyah which is the Frame of Mind, namely thinking using Islamic principles ; 2) Nafsiyah Islamiyah which is the Frame of Work, namely fulfilling physical needs and instincts in accordance with Islamic rules. Meanwhile, to achieve Brand Perception you must go through 3 stages, namely 1) Brand Value, namely how Islamic values are perceived by consumers more than physical expectations; 2) Brand Promise, how to provide consumers with an understanding that the promise of Allah SWT is the most perfect; and 3) Brand Experience, how consumers feel the happiness of meeting Islam so they can face life with struggle and strength. For the highest consumer loyalty is not to the brand, but loyal to Allah SWT.